2020
DOI: 10.35631/ijppsw.25001
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Concept of Policy Transfer: A Systematic Literature Review Approach

Abstract: Policy transfer is not a new concept in public policy or political science research. However, there are many misconceptions about policy transfer from past scholars which fragmented policy understanding among political scientists and researchers. Hence, this paper aims to shed light on the basic concept of policy transfer and add value to the current literature especially in an academic context. This paper employed secondary data from the past ten years (2010-2020) derived from selected published resources of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In short, the researcher searches both databases simultaneously for all relevant keywords related to the research topic. Based on previous systematic review studies, the keywords used can come from thesaurus, variant, related terms, expert opinion, or keywords from previous literature (Mokhtar & Rahman, 2020) (Moher et al, 2009) (Bramer et al, 2017); (Shaffril et al, 2019). The keywords used in this study are: "Policy Transfer".…”
Section: Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In short, the researcher searches both databases simultaneously for all relevant keywords related to the research topic. Based on previous systematic review studies, the keywords used can come from thesaurus, variant, related terms, expert opinion, or keywords from previous literature (Mokhtar & Rahman, 2020) (Moher et al, 2009) (Bramer et al, 2017); (Shaffril et al, 2019). The keywords used in this study are: "Policy Transfer".…”
Section: Identificationmentioning
confidence: 99%
“…For more than 30 years, publications on policy transfer have emerged from the establishment of the concept of policy transfer to applications of policy transfer worldwide (Zhang & Yu, 2021) (Dolowitz, 2017); (Rose, 1991). Many researchers discuss the use of policy transfers from a modern perspective which does not only concentrate on the government but also in terms of private sector practices carried out by many countries in various fields (Mokhtar & Rahman, 2020). (Evans, 2017) revealed that the concept of policy transfer actually existed since the beginning of the Christian era.…”
Section: Introductionmentioning
confidence: 99%